Negative regulation of fibrin polymerization and clot formation by nanoparticles of silver - Shrivastava S.; Singh S.K.; Mukhopadhyay A.; Sinha A.S.K.; Mandal R.K.; Dash D. (My University, 2025)
Thrombolytic therapy in acute stroke has reduced ischemia; however, it is also associated with increased incidence of intracerebral hemorrhage and expanding stroke. Platelets and fibrin are the major components of thrombi. Since fibrin is available in large concentration at lesion sites and in all types of thrombi, it is an obvious target for majority of antithrombotic therapies. Previously we have demonstrated innate antiplatelet properties with nanosilver. It can effectively prevent platelet activation in response to physiological agonists, under both in vitro as well as ex vivo conditions, and immobilize and stabilize proteins. Here we report for the first time that nanosilver can significantly retard fibrin polymerization kinetics both in pure and plasma-incorporated systems and hence can impede thrombus formation. We also discuss the conformational changes ensued upon fibrinogen following interaction with nanosilver. Together with its inherent antiplatelet and antibacterial properties, capacity to inhibit fibrin polymerization can open up possibilities of newer biomedical application and research potential involving silver nanoparticles. © 2010 Elsevier B.V.